Die Anthropologisierung des Ökonomischen in spanischen Komödien, 1762-1805 vom vir oeconomicus bis zur femina profusa - Schuchardt, Beatrice (La Cuestión Palpitante. Los siglos XVIII y XIX en España, 2023)
The political economy of the European 18th century declares economics to be a basic human condition. This phenomenon is summed up in the present study under the term "anthropologizing of the economic" and examines how treatises by Spanish reform economists from the late 18th century are reflected in sentimental economic comedies of the late Enlightenment. For the first time since Schumpeter, the study, located at the interface between literary studies, cultural studies and the history of economic theory, offers a German-language overview of the currents of economic thought in Enlightenment Spain and its predecessors, based on current research. In doing so, she establishes references to developments in France, England and Germany on the levels of economic and theater reform. Based on the knowledge that when talking about economic people (homo oeconomicus), the economic man (vir oeconomicus) is usually meant, she develops a set of conceptual tools for Analysis of the recurring economic character types in Spanish reform theatre. By examining comedies from the period between 1762 and 1805, she differentiates between gender-specific incarnations of good and bad management in trade, industry and agriculture, ranging from the vir oeconomicus to the femina profusa are sufficient. In addition to the transfer processes between economic and theatrical discourse, the study pays special attention to the burgeoning liberalism and to a connection between the economic and the religious that is specific to Spain. For its interdisciplinary character, it was awarded the sponsorship prize of the University Society of Münster e.V